2011
DOI: 10.1308/rcsann.2011.93.6.432
|View full text |Cite
|
Sign up to set email alerts
|

Tennis elbow

Abstract: Tennis elbow is a common condition: one of those aches and pains of middle-aged collagen. Often provoked by overuse but sometimes spontaneous, it is usually a self-limiting condition. However, when symptoms are troublesome patients are likely to seek help at least to tide them over until it settles or if not, to provide a cure. These two papers complement each other and help the reader to consider all the options. In the first article, Messrs Kumar and Stanley give a concise but comprehensive summary of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The technique involves debridement the diseased tendon and cortication of the bone. If moderate or severe injury of the LUCL is not realized before the surgery, it may lead to further destabilization of the elbow [12] . Therefore, the patients with lateral epicondylitis, especially moderate and severe lateral epicondylitis, should be recommended for further MR examination to evaluate the extent of the LUCL injury.…”
Section: Discussionmentioning
confidence: 99%
“…The technique involves debridement the diseased tendon and cortication of the bone. If moderate or severe injury of the LUCL is not realized before the surgery, it may lead to further destabilization of the elbow [12] . Therefore, the patients with lateral epicondylitis, especially moderate and severe lateral epicondylitis, should be recommended for further MR examination to evaluate the extent of the LUCL injury.…”
Section: Discussionmentioning
confidence: 99%
“…In general, imaging is not initially performed, but it is helpful for evaluating disease extent, excluding other elbow joint diseases, and for surgical planning. Magnetic resonance imaging (MRI) is the most widely used imaging modality and has high sensitivity, specificity, and accuracy for diagnosing lateral epicondylitis 4, 5, 6. CET injury is a characteristic imaging finding of lateral epicondylitis, and previous studies have shown a radial collateral ligament (RCL) or lateral ulnar collateral ligament (LUCL) abnormality is a finding that frequently accompanies CET injury 1, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…5 Magnetic resonance imaging (MRI) has an excellent contrast resolution of soft tissue and have demonstrated acceptable levels of sensitivity, specificity, and accuracy in the diagnosis of lateral epicondylitis. 6 8 However, few studies has determined the inter-reliability and intra-reliability for lateral epicondylitis and relationship between MRI abnormalities of the CET and the patient's clinical symptom.…”
Section: Introductionmentioning
confidence: 99%